Insertion of Badnaviral DNA in the Late Blight Resistance Gene (R1a) of Brinjal Eggplant (Solanum melongena) - Serfraz, Saad; Sharma, Vikas; Maumus, Florian; Aubriot, Xavier; Geering, Andrew D. W.; Teycheney, Pierre-Yves (Frontiers in Plant Science, 2021)
Endogenous viral elements (EVEs) are widespread in plant genomes. They result from the random integration of viral sequences into host plant genomes by horizontal DNA transfer and have the potential to alter host gene expression. We performed a large-scale search for co-transcripts including caulimovirid and plant sequences in 1,678 plant and 230 algal species and characterized 50 co-transcripts in 45 distinct plant species belonging to lycophytes, ferns, gymnosperms and angiosperms. We found that insertion of badnavirus EVEs along with Ty-1 copia mobile elements occurred into a late blight resistance gene (R1) of brinjal eggplant (Solanum melongena) and wild relatives in genus Solanum and disrupted R1 orthologs. EVEs of two previously unreported badnaviruses were identified in the genome of S. melongena, whereas EVEs from an additional novel badnavirus were identified in the genome of S. aethiopicum, the cultivated scarlet eggplant. Insertion of these viruses in the ancestral lineages of the direct wild relatives of the eggplant would have occurred during the last 3 Myr, further supporting the distinctiveness of the group of the eggplant within the giant genus Solanum.